(untitled) (New York, 2012)
The book is an analysis of commercial arbitration law and practice in South Korea, presenting in an accessible, yet comprehensive manner, the country s arbitration law, the major Korean arbitration institution and its rules, relevant court rulings, etc. It includes a historical and legal overview and discussion of the rise and breadth of the use of commercial arbitration in Korea. Arbitration Law of Korea: Practice and Procedure covers all of the essential topics, including arbitration agreements, arbitral tribunals, arbitral awards, arbitration procedures, enforcement of awards, supportive roles played by the courts, etc. The book also contains new and improved complete translations of the Arbitration Act and the arbitration rules of the Korean Commercial Arbitration Board
Keywords: Trọng tài và giải thưởng,Arbitration and award; Hàn Quốc,Korea